Stimulation of Treg Cells to Inhibit Osteoclastogenesis in Gorham-Stout Disease - Rossi, Michela; Rana, Ippolita; Buonuomo, Paola Sabrina; Battafarano, Giulia; De Martino, Viviana; D’Agostini, Matteo; Porzio, Ottavia; Cipriani, Cristiana; Minisola, Salvatore; De Vito, Rita; Vecchio, Davide; Gonfiantini, Michaela Veronika; et al. (Frontiers in Cell and Developmental Biology, 2021)
Gorham-Stout disease (GSD) is a very rare syndrome displaying excessive bone erosion and vascular lesion. Due to the rarity of the disease and to the limited studies, its etiopathogenesis is not entirely known. The involvement of immune system in the progressive osteolysis was recently suggested. Indeed, extensive reciprocal interactions between the immune and skeletal systems have been demonstrated. This study aimed to evaluate alterations of immune cells in GSD. An increase of CD8+ cells and reduction of CD4+ and CD4+CD25+CD127low cells was revealed in patients. Interestingly, patients’ regulatory T cells maintain the ability to respond to extracellular stimuli and to regulate osteoclastogenesis; GSD cells proliferate under aCD3/CD28 signal reaching similar levels to those observed in control culture and exert their immunomodulatory activity on effector T cells. GSD Treg cells preserved their inhibitory effects on the osteoclastogenesis. These results suggest that stimulation of Treg cells could open the way for the identification and testing of new therapeutic approaches for patients affected by Gorham-Stout disease.